2019
DOI: 10.1007/s10353-019-0598-5
|View full text |Cite
|
Sign up to set email alerts
|

Imaging response evaluation after novel neoadjuvant treatments of pancreatic cancer

Abstract: Background Emergent neoadjuvant concepts have improved the rate of margin-free (R0) resections in borderline resectable and locally advanced pancreatic ductal adenocarcinoma. However, due to specific properties of pancreatic cancer, imaging response assessment is difficult. Methods The concepts of histologic response patterns and their imaging correlates are outlined, together with efforts in morphologic and functional imaging to overcome the challenges of response assessment. Results Imaging evaluation after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
4
0
1
Order By: Relevance
“…To overcome the limitations of radiologic response evaluation, several alternative assessment methods have been investigated (83)(84)(85). A recent prospective study suggested that partial regression of tumor contact with vascular structures on pancreatic CT indicates a high likelihood of R0 resection and suitability for surgical exploration (86).…”
Section: Resectability Evaluation In Patients Receiving Neoadjuvant Treatmentmentioning
confidence: 99%
“…To overcome the limitations of radiologic response evaluation, several alternative assessment methods have been investigated (83)(84)(85). A recent prospective study suggested that partial regression of tumor contact with vascular structures on pancreatic CT indicates a high likelihood of R0 resection and suitability for surgical exploration (86).…”
Section: Resectability Evaluation In Patients Receiving Neoadjuvant Treatmentmentioning
confidence: 99%
“…112 La RM con secuencias de difusión no ha demostrado mejores resultados que los hallazgos mencionados en TCMS. 113 Algunos autores han demostrado el potencial valor del PET TC con FDG para evaluar objetivamente la respuesta a la quimiorradioterapia.…”
Section: • ¿Cómo Se Evalúa La Respuesta Al Tratamiento En Un Paciente Con Acdp Borderline O Inoperable En Protocolo De Rescate Con Quimiounclassified
“…The majority of patients present with distant metastatic disease at the time of diagnosis and around one third of cases present with locally advanced disease [8]. Due to the increasing availability of diagnostic tools like computed tomography (CT), an increasing number of patients are diagnosed in an early locally advanced stage of disease and therefore qualify for neoadjuvant therapy, which has emerged as a standard treatment in borderline resectable PDAC [6,9]. Although novel therapeutic combinations based on gemcitabine or FOLFIRINOX have shown promising results in all stages of disease, a large number of patients suffer from little to no efficacy based on the development of chemoresistance [10].…”
Section: Original Articlementioning
confidence: 99%